Impartiality in police interpreting - Ortiz Soriano, Adela (MonTi Monografías de Traducción e Interpretación, 2016)
The different codes of ethics applicable to interpreting in police settings include principles – confidentiality, fidelity, impartiality – that every interpreter should obey. The police setting, however, creates situations in which it is not possible to follow these principles. Taking this contradiction as a starting point, and focusing on the principle of impartiality, the aim of this study is to verify if there is, indeed, a divorce between theory and practice and to establish what determines the eventual divergence. In order to validate the hypothesis, the study describes five interpreting sessions between French and Spanish that took place at different police stations in Valencia. The data were collected by means of a questionnaire filled in by the interpreter-researcher. The results show that there is in fact a divorce between theory and practice and the analysis suggests the possible causes behind the tensions that the interpreter encounters when trying to keep the principle of impartiality in police interpreting.